LAIR-1 Limits Neutrophilic Airway Inflammation - Kumawat, Kuldeep; Geerdink, Ruben J.; Hennus, Marije P.; Roda, Mojtaba Abdul; van Ark, Ingrid; Leusink-Muis, Thea; Folkerts, Gert; van Oort-Jansen, Anita; Mazharian, Alexandra; Watson, Steve P.; Coenjaerts, Frank E.; Bont, Louis; et al. (Frontiers in Immunology, 2019)
Neutrophils are crucial to antimicrobial defense, but excessive neutrophilic inflammation induces immune pathology. The mechanisms by which neutrophils are regulated to prevent injury and preserve tissue homeostasis are not completely understood. We recently identified the collagen receptor leukocyte-associated immunoglobulin-like receptor (LAIR) -1 as a functional inhibitory receptor on airway-infiltrated neutrophils in viral bronchiolitis patients. In the current study, we sought to examine the role of LAIR-1 in regulating airway neutrophil responses in vivo. LAIR-1-deficient (Lair1-/-) and wild-type mice were infected with respiratory syncytial virus (RSV) or exposed to cigarette smoke as commonly accepted models of neutrophil-driven lung inflammation. Mice were monitored for cellular airway influx, weight loss, cytokine production and viral loads. After RSV infection, Lair1-/- mice show enhanced airway inflammation accompanied by increased neutrophil and lymphocyte recruitment to the airways, without effects on viral loads or cytokine production. LAIR-1-Fc administration in wild type mice, which blocks ligand induced LAIR-1 activation, augmented airway inflammation recapitulating the observations in Lair1-/- mice. Likewise, in the smoke-exposure model, LAIR-1 deficiency enhanced neutrophil recruitment to the airways and worsened disease severity. Intranasal CXCL1–mediated neutrophil recruitment to the airways was enhanced in mice lacking LAIR-1, supporting an intrinsic function of LAIR-1 on neutrophils. In conclusion, the immune inhibitory receptor LAIR-1 suppresses neutrophil tissue migration and acts as a negative regulator of neutrophil-driven airway inflammation during lung diseases. Following our recent observations in humans, this study provides crucial in-vivo evidence that LAIR-1 is a promising target for pharmacological intervention in such pathologies.